eliminate theta between a=cos(theta-alpha) and b=sin(theta-beta)

Theta – Alpha = cos^-1(a) (equ.1)
Theta – Beta = sin^-1(b) (equ.2)
Subtracting the equations, we get
Beta – Alpha = cos^-1(a) – sin^-1(b)

Was this answer helpful?

  
   

0 (0)

Upvote (0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question